Distance measurements based on road infrastructure indicators characteristics affecting purchasing decision of affordable housing in northern states of peninsular Malaysia/ Muhamad Hilmi Mohamad @ Masri ... [et al.] - Mohamad @ Masri, Muhamad Hilmi; Sa’ad, Mohd Farid; Azman, Najma; Aliasak, Mohd Hasrol Haffiz; Mohd Lazi, Mohd Khairul Afzan; Md Wadzir, Mohammad Fitry (Universiti Teknologi MARA, Perak, 2024)
The research is aimed at distance measurements based on road infrastructure indicators characteristics affecting the purchasing decision of affordable housing in northern states of Peninsular Malaysia. The objectives of this research are to measure road infrastructure indicators relating to distance and affordable housing and to analyse the relationship between road infrastructure indicators on distance and affordable housing. Structural Equation Modelling was utilized in this research for analysis and findings whilst discussions conducted on significant level measurement based on each indicator. The significance of the research is to help everyday commuters in making better decision-making processes to purchase affordable houses that they are comfortable with in their daily travels. Affordable houses at a closer rate therefore can contribute significant positive effects on pollution emissions by private vehicles travelling long distances daily thus achieving greener results.